Avaliação de diferentes sistemas de preparo do solo no desenvolvimento inicial de Eucalyptus benthamii Maiden et Cambage na região de Guarapuava, PR. - Bernardi, Carlos Alberto (2010)
The soil tillage in forestry have the objective of improving the plants growing. In this study it was analyzed the influence of four different soil preparation methods on the initial development of Eucalyptus benthamii Maiden et Cambage. The treatments used in the planting were: planting without any kind of preparation; semi mechanical hole-digging; subsoiling with a bulldozer; subsoiling with farm tyres tractor. The delineation applied was randomized blocks, where four repetitions were used for growing evaluation and two ones to the root system evaluation. The growing tests were made a two months` period during the year. For root development it was realized a visual evaluation two and four months after the plantation. Six and eight months after, was realized an statistical analyze from the collected data. It was used the BARTLETT method to measure the homogeny of variation. ANOVA to test the homogeny average and the DUNCAN test for averages confront. The results shown that: two months after the plantation no significant difference was detected among the treatments which referees to the plant growing; in the analyses realized at two and 10 months after the plantation always occurs some significant difference for the more intensive soil preparation with better results comparing with the others treatments in some parameters analyzed (diameter , high and crown diameter); finally in 12 months evaluation no significant difference was perceived among the different treatments. On the root system evaluation the only significant difference was the sub soiling with a bulldozer. This study shows that a more intensive tillage works better on the root system development. On the other hand it wasn`t possible to prove, trough this study, the influence of the treatment on the seedlings development in plantations of one year old. Nevertheless, two points must be observed: the best results of intense soils treatment from two to 10 months after the plantation and, the best development of the root system in subsoiling treatment, what can represents better seedling or plant sustentation due to an a bigger volume of soil explored for nutrition and root growth.